Transformational leadership and employees' helping and innovative behaviors: contextual influences of organizational justice - Lim, Jae Young; Moon, Kuk-Kyoung (International journal of manpower, 2022)
PurposeThis article explores whether transformational leadership (TFL) influences individuals' extra-role behaviors, specifically helping and innovative behaviors. More importantly, it focuses on whether TFL's influence on employees' helping and innovative behaviors is contingent upon two subdimensions of organizational justice (OJ): distributive justice (DJ) and procedural justice (PJ).Design/methodology/approachThe authors relied on the 2017 Korean Public Employee Viewpoint Survey conducted by the Korea Institute of Public Administration (KIPA), which is based on stratified, two-stage cluster sampling. Because the dependent variables for the empirical models were summed averages, the authors used OLS as a statistical method. The regression was performed using Stata 14.FindingsThe results revealed that TFL was positively associated with both helping and innovative behaviors. When moderated by DJ, TFL has a positive impact only on helping behavior. However, when moderated by PJ, TFL has a positive influence on both behaviors.Research limitations/implicationsTFL was measured using four items. While the measure reflects four dimensions of TFL, its construct validity may be subject to criticism. Relying on a one-year cross-sectional dataset means that this study's findings might not be fully generalizable to all public sector environments across different cultures.Practical implicationsThis article's findings on how TFL is contextualized under different OJ contexts will help advance understanding of how it works in contemporary public organizations.Originality/valueDespite the importance of OJ as a vital heuristic that reshapes employees' perceptions of their organizations, few studies have focused on how it can moderate the relationship between TFL and employees' extra-role behaviors. By investigating such moderating effects, this study advances the scholarly understanding of boundary conditions that affect TFL and its effectiveness in organizational settings. It utilizes a South Korean survey, which brings an international perspective to this understanding.